The diachronic view of nasality – from Latin to Brazilian Portuguese - Rodrigues, Tatiana Bermond dos Santos (RCMOS - Revista Científica Multidisciplinar O Saber, 2025)
This paper, derived from Rodrigues’ (2013) Master’s Thesis, which investigates vocalic nasality in the Andirá community in Barreirinha, Amazonas, presents a bibliographical survey, covering historical authors of the Portuguese language, such as Melo (1967), Williams (1961), Faria (1970), Nobiling (1907), Bueno (1967), among others. The study shows that nasality, which was absent in Latin (the language from which Portuguese originated), emerged in Old Portuguese as a result of evolutionary transformations. The current research reveals a notable similarity between the nasality produced in Barreirinha and that documented in Lisbon-Coimbra during the Old Portuguese period. The central phenomenon addressed in Barreirinha is the non-nasalization of vowels, or a more oral than nasal production, in phonological contexts that, by the conventions of Brazilian Portuguese, should present some degree of nasalization. This work thus reinforces the undeniable evolution from Latin to Portuguese, with Latin phonological environments giving rise to nasality in Brazilian Portuguese over time.